PENGARUH PENGUNAAN ECU STANDAR DAN ECU RACING BRT TERHADAP UNJUK KERJA MOTOR VIXION 2019 - Cecep Nana Nasuha; Agus Adi Nursalim; Mamat Haerudin (Jurnal Fakultas Teknik Kuningan, 2022)
The increasing number of motorcycles with EFI systems has caused conventional motorcycles that use the carburetor system to be abandoned. This is because the motorcycle with a carburetor system still has many shortcomings. Among them require routine maintenance on the carburetor system, more wasteful fuel consumption, and it is difficult to control the air and fuel mixture that must be set manually. The engine performance produced by the injection motorcycle is less than the maximum. This can be caused by the lack of fuel intake that is sprayed by the injector and the short injection duration. From these problems, the authors intend to conduct research on the effect of using the Standard ECU and ECU Racing on motorcycle performance by testing on a Yamaha V-Ixion motorcycle. This study aims to determine the effect of using the standard ECU and Juken ECU with injector variations on the torque and power of a Yamaha V-Ixion motorcycle. The study used a Yamaha V-Ixion motorcycle. The method used in this research is experimental. The results showed that the use of a standard injector standard ECU obtained a maximum torque of 0.0527 Nm and a maximum power of 0.0402 HP, while the racing ECU produced the highest torque of 0.1897 Nm and a power of 0.1445 HP. Based on the test results, it can be concluded that the use of the Juken injector racing ECU has an effect in increasing the torque and power of the injection motorcycle.